2003
DOI: 10.1111/1467-8624.00518
|View full text |Cite
|
Sign up to set email alerts
|

School–Based Early Intervention and Later Child Maltreatment in the Chicago Longitudinal Study

Abstract: Investigated were the effects of participation in the Title I Child-Parent Centers (CPC) on substantiated reports of child maltreatment for 1,408 children (93% of whom are African American) in the Chicago Longitudinal Study. The CPCs provide child education and family support services in high-poverty areas. After adjusting for preprogram maltreatment and background factors, 913 preschool participants had significantly lower rates of court petitions of maltreatment by age 17 than 495 children of the same age wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
144
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 155 publications
(157 citation statements)
references
References 53 publications
12
144
0
1
Order By: Relevance
“…16,18 Statistical Analysis 34,35 SEs and significance tests were adjusted for variation among sites by using the HuberWhite/sandwich correction. 32,33 As observed in previous studies, [16][17][18][19][20][21] coefficients were robust to alternative covariates and model specifications. Given the relatively high levels of fidelity of program implementation, site-to-site variation in outcomes was modest.…”
Section: Parental Involvementsupporting
confidence: 51%
See 2 more Smart Citations
“…16,18 Statistical Analysis 34,35 SEs and significance tests were adjusted for variation among sites by using the HuberWhite/sandwich correction. 32,33 As observed in previous studies, [16][17][18][19][20][21] coefficients were robust to alternative covariates and model specifications. Given the relatively high levels of fidelity of program implementation, site-to-site variation in outcomes was modest.…”
Section: Parental Involvementsupporting
confidence: 51%
“…Participation beginning in preschool was found to eliminate the achievement gap in school readiness and early performance, reduce rates of child maltreatment and school remedial education, reduce rates of felony arrest and substance abuse, and increase rates of high school graduation. [15][16][17][18][19] Economic benefits were found to exceed costs by a ratio of 7-to-1 or higher. [20][21][22] Although these findings provide a foundation for expansion, the contemporary context of early childhood programs are different than in the 1980s.…”
Section: Child-parent Center Program and Scale Upmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported benefits of educational intervention to address deficits in early literacy include fewer referrals for special education services, reduced grade retention rates, increased graduation rates, and less juvenile delinquency. 39 Further research is needed to determine the effect of refractive correction on these educational deficits. It is important to determine whether correction of hyperopia may benefit preschool children by improving their ability to perform visually and academically.…”
Section: Pagementioning
confidence: 99%
“…[69][70][71] Although pediatricians have long been familiar with therapeutic preschools and with parenting programs, study results have suggested that these interventions are more effective when multiple modalities are combined with those that target the entire family. Reynolds and Robertson 72 reported that participation in school-based child-parent centers, which provided extensive family education and support, reduced maltreatment by 50% in a population at high risk. Other study results have shown significant effects when community-based parent-child interventions are targeted at specific populations, combine peer and professional support, and provide some services directly to the children.…”
Section: Community Prevention Programs and Resourcesmentioning
confidence: 99%